Penerapan Metode Kerja Kelompok dalam Pembelajaran IPA Materi Alat Reproduksi Manusia pada Siswa Kelas 9A SMPN 19 Bandar Lampung - Romala, Romala (STKIP PGRI Bandar Lampung, 2022)
Science education emphasizes providing direct experience to develop competence so that students are able to explore and understand the natural surroundings scientifically. Teaching that only uses the lecture method will make it difficult for students to understand concepts in science lessons, so students are less enthusiastic in learning activities and are passive. Students only memorize so they do not understand the concept. This is due to the assumption that knowledge can be transferred from one person's mind to another's mind, so that teachers who are active in learning to transfer their knowledge such as machines, they listen, take notes, and do the tasks given by the teacher, so that learning is teacher-centered and understanding. The results achieved by students are instrumental. The purpose of this study is to approach group work to improve student activity and learning outcomes in science learning on the material of excretory organs in humans and their functions for class VIII students of SMP Negeri 9 Bandar Lampung. The method used in this study is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and Reflection. in learning science on the material of excretory organs in humans and their functions for class VIII students of SMP Negeri 9 Bandar Lampung. Furthermore, the researcher recommends: (1) For teachers who have the same difficulty, the approach to group work is to increase student activity and learning outcomes in science learning on the excretory organs in humans and their functions. (2) In order to get maximum results, it is hoped that teachers will make PBP more interesting and varied.